Development of an underactuated exoskeleton for effective walking and load-carrying assist. (17th April 2016) - Yu, Seungnam; Lee, Heedon; Kim, Wansoo; Han, Changsoo
Abstract: This study proposed and developed an underactuated exoskeleton to support external load-carrying and partial assist for leg motion with level walking and ascending of slopes and stairs, which require positive energy generation. A strategy for active and passive joint combination are implemented on the underactuated exoskeleton, along with a quasi-passive mechanism to assist with vertical weight support and gait propulsion while minimizing hindrance to the wearer's free motion. Further, muscle circumference sensors are directly matched with the active joint system, and insole sensors are applied to efficiently detect the wearer's motion intension. Through experiments with the developed exoskeleton system, the considered performances were verified by analyzing the electromyography data from the rectus fremoris and gastrocnemius muscles while walking and ascending stairs. The developed underactuated exoskeleton can assist healthy people's load-carrying and facilitate efficient ascension by utilizing the structural body weight support, leg swing, and lifting motion assist through motorized knee joints only. This kind of active joint minimization approach could be particularly helpful in field applications that require independent power sources such as batteries. Abstract :